Modulation of Gene Expression in Actinobacteria by Translational Modification of Transcriptional Factors and Secondary Metabolite Biosynthetic Enzymes - Martín, Juan F.; Liras, Paloma; Sánchez, Sergio (Frontiers in Microbiology, 2021)
Different types of post-translational modifications are present in bacteria that play essential roles in bacterial metabolism modulation. Nevertheless, limited information is available on these types of modifications in actinobacteria, particularly on their effects on secondary metabolite biosynthesis. Recently, phosphorylation, acetylation, or phosphopantetheneylation of transcriptional factors and key enzymes involved in secondary metabolite biosynthesis have been reported. There are two types of phosphorylations involved in the control of transcriptional factors: 1) phosphorylation of sensor kinases and transfer of the phosphate group to the receiver domain of response regulators, which alters the expression of regulator target genes. 2) Phosphorylation systems involving promiscuous serine/ threonine/tyrosine kinases that modify proteins at several amino acid residues, e.g., the phosphorylation of the global nitrogen regulator GlnR. Another post-translational modification is the acetylation at the epsilon amino group of lysine residues. The protein acetylation/deacetylation controls the activity of many short and long-chain acyl-CoA synthetases, transcriptional factors, key proteins of bacterial metabolism, and enzymes for the biosynthesis of the non-ribosomal peptides, desferrioxamine, streptomycin, or phosphinic acid-derived antibiotics. Acetyltransferases catalyze acetylation reactions showing different specificity for the acyl-CoA donor. Although functions as acetyltransferase, there are examples of malonylation, crotonylation, succinylation, or modification activities, using bulky acyl-CoA derivatives. Substrates activation by nucleoside triphosphates is one of the central reactions inhibited by lysine acetyltransferases. Phosphorylation/dephosphorylation or acylation/deacylation reactions on global regulators like PhoP, GlnR, AfsR, and the carbon catabolite regulator glucokinase strongly affects the expression of genes controlled by these regulators. Finally, a different type of post-translational protein modification is the phosphopantetheinylation, catalysed by PPTases. This reaction is needed to modify those enzymes requiring phosphopantetheine groups like non-ribosomal peptide synthetases, polyketide synthases, and fatty acid synthases. Up to five PPTases are present in S. tsukubaensis and S. avermitilis. Different PPTases modify substrate proteins in the PCP or ACP domains of tacrolimus biosynthetic enzymes. Directed mutations of genes encoding enzymes involved in the post-translational modification is a promising tool to enhance the production of bioactive metabolites.